2011
DOI: 10.1111/j.1477-2574.2011.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia negatively impacts short-term outcomes in patients undergoing hepatic resection for colorectal liver metastasis

Abstract: Sarcopenia impacts short-, but not long-term outcomes after resection of CRLM. While patients with sarcopenia are at an increased risk of post-operative morbidity and longer hospital stay, long-term survival is not impacted by the presence of sarcopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
377
12
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 375 publications
(413 citation statements)
references
References 44 publications
22
377
12
2
Order By: Relevance
“…Further studies are necessary to clarify how sarcopenia increases the risk of infectious complications after gastric cancer surgery. In the present study, the LBM as measured by BIA was not a significant risk factor for surgical morbidity, which was contradictory to the previous studies evaluating the slices examined by computed tomography (CT) [11,12]. This discrepancy could be explained by the difference in the characteristics of the cohort and the methodological difference.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Further studies are necessary to clarify how sarcopenia increases the risk of infectious complications after gastric cancer surgery. In the present study, the LBM as measured by BIA was not a significant risk factor for surgical morbidity, which was contradictory to the previous studies evaluating the slices examined by computed tomography (CT) [11,12]. This discrepancy could be explained by the difference in the characteristics of the cohort and the methodological difference.…”
Section: Discussioncontrasting
confidence: 99%
“…HGS would have a great advantage to select patients with good performance status but high risk for morbidity. Previous studies for other upper abdominal surgery such as hepatocellular carcinoma, pancreas cancer, and metastatic liver tumor demonstrated that sarcopenia was a risk factor for postoperative complication [12,35,36]. However, no report showed a correlation of sarcopenia and respiratory complications, which is different from the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although in some studies a correlation between PA and post‐operative complications was seen, the majority have failed to prove a relationship between PA‐assessed sarcopenia and survival 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23. Only few have actually assessed the agreement between PA and SMA within their population; Jones et al studied 100 patients with colorectal cancer and reported a Spearman correlation of 0.8 for PA and SMA and a Spearman correlation of 0.94 for PA and PLW, which could not be reproduced in our cohort 11.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been used to predict surgical complications in different cancer types with contrasting results. PA has shown a correlation with post‐operative complications in individual studies on colorectal cancer, colorectal liver metastases, kidney cancer, bladder cancer, cholangiocarcinoma, and hepatocellular cancer,11, 12, 13, 14, 15, 16 while this effect was not seen in other pancreatic cancer, endometrial cancer, biliary cancer, or sarcoma studies 17, 18, 19, 20. Interestingly, only few cancer studies were able to show a correlation between PA and survival 21, 22, 23.…”
Section: Introductionmentioning
confidence: 99%